2020
DOI: 10.51386/25815946/ijsms-v3i4p112
|View full text |Cite
|
Sign up to set email alerts
|

Work-Family Conflict and Worker’s Performance during Covid-19 Pandemic: What is the Role of Readiness to Change Mentality?

Abstract: This study aimed to measure the effect of work-family conflict on employee performance of the part-time employee of a packaging industry in Tangerang which are mediated by readiness for change. Data collection during covid-19 pandemic was done by simple random sampling technique and the returned and valid questionnaire results were 143 samples. Data processing was used SEM method with Smart PLS 3.0 software. The results of this study concluded that work-family conflict have negative and significant effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 9 publications
5
40
3
3
Order By: Relevance
“…Teachers have also mentioned the importance of proper supervisory actions (support and appreciation), opportunity to learn (training), and team support (colleagues) repeatedly. In this sense, various themes and keywords that are highlighted in Table 1 have been derived as vital concepts for wellbeing of teachers during the pandemic, which is linked to the extant literature ( Rasool et al, 2019 , 2022 ; Novitasari et al, 2020 ; Vaziri et al, 2020 ; Andrade and Petiz Lousã, 2021 ; Ghislieri et al, 2021 ). Notably, lack of information, functionality of online platforms for learning, and having to deal with family-related matters during work hours have been among the factors that not only caused stress and/or conflict, but further had a vivid impact on their motivation, engagement, and overall performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teachers have also mentioned the importance of proper supervisory actions (support and appreciation), opportunity to learn (training), and team support (colleagues) repeatedly. In this sense, various themes and keywords that are highlighted in Table 1 have been derived as vital concepts for wellbeing of teachers during the pandemic, which is linked to the extant literature ( Rasool et al, 2019 , 2022 ; Novitasari et al, 2020 ; Vaziri et al, 2020 ; Andrade and Petiz Lousã, 2021 ; Ghislieri et al, 2021 ). Notably, lack of information, functionality of online platforms for learning, and having to deal with family-related matters during work hours have been among the factors that not only caused stress and/or conflict, but further had a vivid impact on their motivation, engagement, and overall performance.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, having a better approach toward challenges in their personal aspects of lives. Organizational support and various Human Resource Management (HRM) practices also have been reported to be influential in this context ( Rasool et al, 2019 , 2022 ; Novitasari et al, 2020 ; Vaziri et al, 2020 ; Andrade and Petiz Lousã, 2021 ; Ghislieri et al, 2021 ).…”
Section: Literature Review and Theoretical Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the pandemic influenced all labor market-related indicators, such as average salary (Qian & Fan, 2020 ), underemployment (Kawohl & Nordt, 2020 ), hiring rates, the occurrence of work-family conflict (Charoensukmongkol & Puyod, 2021 ; Novitasari et al, 2020 ), absenteeism (Der Feltz-Cornelis et al, 2020 ) and psychological impairment (Salman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Everyone supportive of transformational leadership believes that transformative leaders reinforce faith, loyalty, appreciation, and respect in their followers, as well as between followers and leaders so that they are willing to achieve organizational goals and objectives, purpose, and vision. Previous research has found a positive relationship between transformational leadership and organizational success, both with and without mediation (Kamar et al 2020;Novitasari & Asbari 2020a;Purwanto et al 2019). Therefore, this research proposed: H1: transformational leadership affects work performance Bass (1985) described that transformational leadership consists of four indicators, including individual consideration, intellectual stimulation, idealized influence, and leader inspiration.…”
Section: Introductionmentioning
confidence: 88%